Evaluation of anti - inflammatory activity of adhatoda zeylanica (medic.) Leaves extract - K. ALAM,; D. PATHAK,; S. H. ANSARI, (International Journal of Pharma and Bio Sciences, 2011)
Adhatoda zeylanica (Medic.) family-Acanthaceae is distributed all over the plains of India and lower Himalaya ranges, ascending to height of 1500 m. The present study is an attempt to explore the anti-inflammatory activity of ethanolic and aqueous extract of leaves of the Adhatoda zeylanica. Dose of 100 mg/ml and 200 mg/ml of ethanolic and aqueous extract were evaluated for their anti-inflammatory activity against carrageenan induced paw edema in rat. Both the extracts were able to show anti-inflammatory activity in dose dependant manner as compared to standard drug diclofenac sodium 100 mg/ml. The data were found statistically significant by using one way ANOVA (P< 0.001).